Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Perilaku Konsumtif Pada Siswa SMK Bandara Tangerang - Tiara Indah Pratiwi; Usran Masahere (Tamilis Synex: Multidimensional Collaboration, 2024)
Low financial literacy supported by a high lifestyle causes students to behave consumptively. This study aims to analyze how much influence financial literacy and lifestyle have on consumptive behavior in Tangerang Airport Vocational School students. The method used in this research is quantitative statistics by distributing questionnaires through google form. The population of this study consisted of 100 students of SMK Bandara Tangerang in the academic year 2023 / 2024. The sampling technique used in this study was slovin with a sample size of 80 people. Based on hypothesis testing, this study used the T test and F test. The results showed that there is a positive and significant influence between Financial Literacy on Consumptive Behavior, this is evidenced by the t count of 3.098 > t table 1.991 with a significant level of 0.003 < 0.05 and the significance of lifestyle on consumptive behavior as evidenced by the t count value of 14.984 > t table 1.991 with a significant level of 0.000 < 0.05. Simultaneously, financial literacy and lifestyle are significant to consumptive behavior as evidenced by the value of f count 131.604 > f table 3.12 and Sig value 0.000 < 0.05.